PENGARUH JOB SATISFACTION DAN SELF EFFICACY TERHADAP JOB PERFORMANCE PADA KARYAWAN PT TANJUNG BARU KALIMANTAN SELATAN - Renita Hestiyani; Saladin Ghalib; Jamaluddin Jamaluddin (Universitas Lambung Mangkurat, 2021)
The potential of each source of power humans that exist within the company should be able to be utilized as well as possible, so it is able to provide the results of that maximum. Companies and employees are two things that need each other . If the employee managed to bring progress for the company, profits are obtained will be picked by both sides parties . For employees, the success is aktualisai potential of self as well the opportunity to meet the needs of life. While the company or agency , success is a means towards the growth and development of the company or institution that . Along with its development , the company often times neglect of management source power of man who owned.This study aims to examine the effect of Job Satisfaction (X1) and Self Efficacy (X2) on Job Performance (Y) on Employee PT. Tanjung Baru Kalimantan Selatan. Samples were taken as many as 93 employees using the Slovin formula . Data collection using questionnaire while data analysis using Analysis SmartPLS through the program PLS Version 2.0.The test result proves that Job Satisfaction has a significant effect on Job Performance with the influence of 42,3% including very enough category, Self Efficacy has significant influence to Job Performance with big influence 47,5% including strong enough category, while Self Efficacy significant effect on Job Satisfaction with a large influence 67,2% including very strong categoryKeywords: Job Satisfaction, Self Efficacy, Job Performance